THE POTENTIAL OF POPULATION PROFILES IN STRENGTHENING AND DEVELOPING PRODUCTIVE AND QUALITY YOUNG ENTREPRENEURS FROM AN EDUCATIONAL PERSPECTIVE - Kartika, Tipri Rose (UNIVERSITAS NEGERI SURABAYA, 2025)
Strengthening entrepreneurship is one of the targets in the important agenda in the 2020-2024 RPJMN. Entrepreneurship is not just one virtual world but many worlds, which are starting to form to enable society to deepen and expand social interactions digitally. This study aims to explore the demographic profile and potential of the young generation to develop productive and quality entrepreneurship. Entrepreneurship has a very important role in increasing regional competitiveness, creating jobs, and increasing local revenue (PAD). Each provincial government implements different strategies to promote entrepreneurship development in its region. Mapping entrepreneurial potential, especially among young people, is a strategic step in identifying and optimizing existing resources to create productive and quality young entrepreneurs. Ultimately, this will contribute significantly to economic growth, job creation, and improving the quality of life of the community. Through the right approach, success in developing young entrepreneurship in Indonesia will not only be an opportunity for the individuals concerned, but will also strengthen the foundation of the national economy and increase Indonesia's competitiveness in the international arena.